Developmental Biology and Pathology - Gropp, A. (Springer, 2017)
The early development of the mammalian embryo belongs to a period which, for the student, provides the particularly deep fascination connected with the processes of germination of the fIrst tender buds of life. Moreover, developmental biology encompasses a very large part of biology; if broadly dermed - almost all of it. The same is true for the fIeld of pathology if the manifold possibilities of disorders of the orderly arranged pathways of developmental processes are considered. Normal development in its earliest steps - and it would be diffI cult to see it otherwise - means the functioning of very intricate systems of complex inter dependent cycles controlled by structural, genetic, physiological and biochemical determi nants (...)